Gravimetrical investigation of ice‐rich permafrost within the rock glacier Murtèl‐Corvatsch (upper Engadin, swiss alps) - Daniel S. Vonder Mühll; Emile E. Klingelé (Permafrost and Periglacial Processes)
A gravimetrical study was carried out in the area of the Murtèl‐Corvatsch rock glacier in order to check the applicability of this method in alpine permafrost. The residual anomaly observed after removal of the linear regional trend is up to −1.5 mgal. Cores of borehole 2/1987 through this rock glacier showed a very high ice content in the uppermost 30 m. Borehole geophysical measurements furnished the density distribution with depth at the drill site showing values of less than 1000 kg m−3. According to the core stratigraphy and the density log at the drill site four layers were distinguished: an active layer to 3 m depth; massive ice (3–20 m); an ice‐silt‐sand layer (20–30 m); and a layer with ice‐saturated blocks (30–50 m). The extension of the four distinguished layers is modelled in three dimensions for the entire rock glacier according to the gravity data. The bedrock underneath the creeping permafrost is bowl‐shaped. Une étude gravimétrique a été entreprise sur le glacier rocheux de Murtèl‐Corvatsch (Haute Engadine, Suisse) pour étudier l'applicabilité de la méthode sur le pergélisol alpin. L'anomalie de Bouguer résiduelle, obtenue après soustraction d'un champ régional linéaire, atteint une amplitude maximale de −1.5 mgal. Des carottes du sondage 2/1987, traversant le glacier rocheux, montrent un contenu très élevé en glace dans les premiers 30 m. Des mesures géophysiques faites dans le sondage ont fournis une distribution verticale des densités sur le site, donnant des valeurs inférieures à 1000 kg m−3. A partir de la stratigraphie des carottes et des densités obtenues par géophysique du sondage (density log), quatre couches ont été identifiées: une couche active s'étendant jusqu'à 3 m; une couche de glace massive de 3 à 20 m; une couche mixte glace‐limon‐sable de 20 à 30 m; et enfin une couche de bloc saturée en glace de 30 à 50 m. Les extensions de ces quatres couches ont été modellées en trois dimensions en accord avec les données gravimétriques. La modelisation montre un soubassement du pergélisol en mouvement ayant la forme d'une cuillère.